2007
DOI: 10.1021/jp0669052
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Time-Domain Study of Phonon-Assisted Relaxation of Charge Carriers in a PbSe Quantum Dot

Abstract: The phonon-induced relaxation dynamics of charge carriers in a PbSe quantum dot is studied for the first time by ab initio density functional theory in the time-domain. The picosecond time scale of the relaxation and the absence of the phonon bottleneck are rationalized by relatively high electron and hole state densities. While many of these states show only weak optical activity, most of them participate in the electron-vibrational relaxation. Our simulations demonstrate that the slight asymmetry in the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
155
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(173 citation statements)
references
References 67 publications
(235 reference statements)
17
155
0
Order By: Relevance
“…[22][23][24][25] The core electrons were simulated using the Vanderbilt pseudopotentials, 26 and all valence electrons were treated explicitly. The generalized gradient functional of Perdew and Wang (PW91) 27 was used to account for the electron exchange and correlation effects.…”
Section: Methods and Simulation Detailsmentioning
confidence: 99%
“…[22][23][24][25] The core electrons were simulated using the Vanderbilt pseudopotentials, 26 and all valence electrons were treated explicitly. The generalized gradient functional of Perdew and Wang (PW91) 27 was used to account for the electron exchange and correlation effects.…”
Section: Methods and Simulation Detailsmentioning
confidence: 99%
“…A complete understanding of cooling in NCs that is consistent with all experimental observations is still lacking [55]. A recent calculation of carrier relaxation in PbSe NCs based upon a time-dependent density functional theory [35] found that the density of states is much greater than what is typically assumed, but that most of these states are dark and do not contribute to the absorption spectrum. These dark states are coupled to light states via a variety of NC vibrations (phonons) and can therefore participate in carrier relaxation.…”
Section: Carrier Cooling In Semiconductor Ncsmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 27 Recently, a nonadiabatic molecular dynamics method was established [39,102] in order to simulate the electron relaxation process in QDs [103][104][105]. The method has been used to investigate different systems, as discussed below.…”
Section: Electron-phonon Relaxationmentioning
confidence: 99%
“…The method has been used to investigate different systems, as discussed below. For further reading, please, consult references [39,46,[103][104][105][106][107][108][109][110][111][112][113].…”
Section: Electron-phonon Relaxationmentioning
confidence: 99%
See 1 more Smart Citation